2014
DOI: 10.1159/000360294
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Genitourinary and Gastrointestinal Complications in Open and Endoscopic Gynecologic Cancer Surgery

Abstract: Objectives: The purpose of this study was to examine the incidence of genitourinary and intestinal tract injuries in an effort to identify which factors might predispose a patient to developing one of these surgical complications. Methods: We retrospectively evaluated the charts of gynecologic cancer patients who were treated at a single medical institution from January 2002 to February 2011. The following study variables were noted for evaluation: age, BMI, cancer origin, disease recurrence, a history of pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
5
2
3
Order By: Relevance
“…It is stated that adhesions, previous surgery and endometriosis may increase the risk of bladder injury [13,14]. However, our data do not support this, since there was no significant difference between the two groups.…”
Section: Stage Of Endometriosis (N = 200)contrasting
confidence: 89%
See 2 more Smart Citations
“…It is stated that adhesions, previous surgery and endometriosis may increase the risk of bladder injury [13,14]. However, our data do not support this, since there was no significant difference between the two groups.…”
Section: Stage Of Endometriosis (N = 200)contrasting
confidence: 89%
“…However, our data do not support this, since there was no significant difference between the two groups. Urinary tract injuries occurred equally in the two groups and the frequencies of 1,5% were comparable to the figures of 1,1% in a recent study of Rettenmaier et al [14] . Intestinal injury occurred in 6.5% of the patients with endometriosis and in 5.5% of the control patients.…”
Section: Stage Of Endometriosis (N = 200)supporting
confidence: 85%
See 1 more Smart Citation
“…[1][2][3][4] In our study, we found the rate of all iatrogenic GU injuries occurring during colorectal surgeries to be only 0.18%. Slight variance of these rates within single-institution studies is to be expected, as many factors can alter the prevalence of iatrogenic injury.…”
Section: Discussionmentioning
confidence: 95%
“…The rates of total GU injuries during gynecologic surgery have been previously reported and range from 0.79-8.3%. 1 Most injuries involve the bladder. While the rate of total GU injuries is unknown for colorectal surgery, the rate of ureteral injuries specifically has been reported to be 0.24-5%.…”
mentioning
confidence: 99%